Радиоакустический измеритель скорости и сдвига ветра в атмосферном пограничном слое - Зубков, О. В.; Сидоров, Г. И.; Величко, С. А. (ХНУРЭ, 2008)
The results presented in this paper concern the possibility to develop a radio acoustic system for vertical sounding of atmosphere boundary layer in order to measure horizontal wind speed and wind shear above runway. The objective is to provide aircrafts takeoff/landing with meteorological data. Antennas placement scheme and their parameters are shown, the movement process of acoustic wave packet sent out vertically has been described, as well as its displacement caused by horizontal wind. Then, it has been explained the technique of acoustic packet current coordinates measurement, determination of horizontal wind speed vector components and wind vertical shear. The results of metrological performance studying of the radio acoustic measurer are given.
Keywords: измеритель скорости; тмосферный пограничный слой; сдвиг ветра